Pengaruh Pelatihan Pertolongan Pertama Pada Kecelakaan Terhadap Pengetahuan Penanganan Fraktur Pada Anggota PMR Di SMP Negeri 2 Kuta Utara. - Putu Sumadi; Ida Agung Ayu Laksmi; Putu Wira Kusuma Putra; Made Ani Suprapta (Jurnal Keperawatan Muhammadiyah, 2020)
HEALTH INSTITUTIONBINA USADA BALI BACHELOR DEGREE OF NURSING PROGRAM Undergraduate thesis, May 2019 PUTU SUMADI The Effects of First Aid Training on Accident on Knowledge of Fracture Management Members of JRC Junior High School II Kuta Utara xviii + 73 + 8 tables + 3 pictures + 1 diagram + 22 appendices  ABSTRACT                          Accidents in adolescence are problems that require serious handling. One result of an accident can cause a fracture, fainting, and death. First aid is a form of temporary relief measures for victims of accidents that are carried out as quickly as possible before getting serious treatment from calm health. One way to increase knowledge in first aid in accidents is by providing training. The purpose of this study was to determine the effect of first aid training on knowledge of fracture management.               This study used a pre-experimental research design with one group pre-post test design. The sample of this study were 48 JRC members who did not understand the knowledge of fracture management, taken by non-probability sampling method with provocative sampling. Data analysis was tested using the Wilcoxon Test to compare the results of the pretest and posttest.               The results of the statistical test obtained p-value 0,0001 p <0.05. Thus it can be concluded that there is an effect of first aid training on the knowledge of fracture management. Based on the results of these studies it is suggested to be able to understand the material and training that has been obtained and can apply it in daily life if it meets victims who need immediate help. Keywords: first aid, knowledge of fracture management. Literatures:  49 (2009-2018)